Reliability improvement of the electrical distribution system of the Thanaleng Substation in Vientiane capital, Laos - S. Khounnouvong (2018)
© 2015 IEEE. This work presents the reliability improvement of the electrical distribution system of the Thanaleng substation, by simulation analysis using the DIgSILENT Power Factory program. The study considered the outages in the distribution network from temporary and permanent faults. Consequently, outages frequently will directly affect commercial and private electrical consumption. Outages also deteriorate the power quality and reliability of power distribution systems. This paper presents a methodology for the prediction, evaluation and improvement of reliability indices in an electrical distribution system. The methods were based on power interruption analysis, involving the addition of protective equipment, improvement of system budgets and selection and installation of equipment such as re-closers and disconnect switches (DS) to improve the reliability of distribution.